THE COMPRESSIVE STRENGTH ON C-TYPE FLY ASH-BASED GEOPOLYMER MORTAR - Erniati Bachtiar (Lowland Technology International, 2020)
Reducing and replacing the use of cement in construction work is one way to create an environmentally friendly city. Cement production produces the effect of carbon dioxide, which creates a greenhouse effect. It is necessary to utilize renewable resources that can replace the function of cement to reduce pollution. This research aimed to determine the value of crystallization and amorphous in two types of fly ash in South Sulawesi-Indonesia. The materials used in this research are sand, fly ash, Sodium Hydroxide, and Sodium Silicate. Samples using fly ash originating from two different steam power plants, which are named fly ash A and fly ash B. Comparison of chemicals Sodium Hydroxide and Sodium Silicate in the manufacture of activators, is 1: 2. The amount of sand used is 2.75 from the amount of fly ash. There are two variations of Mortar samples, namely samples using fly ash A (FA_A) and fly ash B (FA_B). GM_FAA is the A-fly ash geopolymer mortar, and MG_FAB is the B-Fly ash geopolymer mortar. The results showed that the percentage of crystals and amorphous in A-Fly ash (FA_A) were 51.02% and 48.97%, while B-Fly ash (FA_B) was 51.28% and 48.71%, respectively. The use of FA_A material in the production of geopolymer mortars has a higher strength than mortars that use FA_B. The use of a suitable activator composition in making mortars using FA_A is 10 M Natrium Hidroksida with alkaline Modulus 2, while mortars using FA_B is 6 M Natrium Hidroksida with alkaline modulus 1.5.